2010
DOI: 10.1002/jbmr.161
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin: A gem from the genome leads to bone-building antibodies

Abstract: Discovery of SclerostinG enomics technologies and DNA sequencing have had a transformative impact on biological research, giving us unprecedented access to the genomes of numerous organisms and ushering in such new fields as systems biology (1) and, more recently, synthetic biology. (2,3) In the 1990s, the advent of highthroughput sequencing spurred application of this powerful new technology to the challenging endeavor of trying to understand the genetic basis of various inherited human diseases. One such dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 81 publications
4
72
0
2
Order By: Relevance
“…In contrast to Spp1, r-irisin injections down-regulates sclerostin, a Wnt/β-catenin pathway inhibitor known to negatively regulate bone formation (40)(41)(42). Load-induced decreases in Sost expression have been associated with increased bone formation (43).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Spp1, r-irisin injections down-regulates sclerostin, a Wnt/β-catenin pathway inhibitor known to negatively regulate bone formation (40)(41)(42). Load-induced decreases in Sost expression have been associated with increased bone formation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of sclerostin, one of the Wnt/b-catenin pathway inhibitors, [33][34][35] was found strongly downregulated in tibiae of Irisin-treated mice. 19 In agreement with these results, sclerostin is known as one of the key proteins involved in mechanical loading, as demonstrated by Robling et al, 36 who showed that Sost expression was decreased by loading, resulting in increased bone formation.…”
Section: The Action Of Irisin On Bone-forming Cellsmentioning
confidence: 97%
“…54,58,59 When bone is subjected to loading, SOST expression and sclerostin levels decrease significantly, stimulating osteoblast activity and probably (through an effect on RANKL) inhibiting osteoclasts. 1,60,61 On the other hand, osteocytes have also recently been shown in vivo and in vitro to be the primary expressers of RANKL, a regulator of osteoclast differentiation and activation. 57,58,62,63 RANKL is upregulated (resulting in targeted tissue removal) when osteocytes are damaged, die by apoptosis or experience prolonged loss of mechanical loading, and recent evidence also suggest that osteocyte RANKL may be specifically involved in the remodeling process of cancellous bone.…”
Section: Modeling: Evidence For and Implications In Acellular Bonementioning
confidence: 99%